Antibiotic Spectrum and Stability of Crude Extract of Extracellular Metabolites from Bacillus mageterium LB01-17 - Ding, Cong-Wen; Wei, Luo-Qing; Zhou, Shang-Ze (Asian Journal of Chemistry, 2021)
Crop pathogens including fungi and bacteria seriously affect the quality and yields of agricultural products. The purpose of this study was to detect the antibiotic spectrum of the crude extract of extracellular metabolites produced by Bacillus megaterium LB01-17 and its stability to heat, acid, alkali and ultraviolet light. The methods of mycelium growth rate and inhibitory zones were used to test the antimicrobial activity of the crude extract on 13 kinds of crop pathogenic fungi and 6 kinds of bacteria. The activity stability of the crude extract was determined under different pH values, acid-base environment and UV radiation time with Colletotrichum gloeosporioides in postharvest mango as the indicator strain. The crude extract displayed broad spectrum activity against all tested fungi with the inhibition rate on 5 kinds of fungi more than 83 %. Inhibitory effects of the crude extract on the growth of 6 kinds of bacteria were also observed and strongest inhibition to Xanthomonas oryzae pv.oryzae in rice was showed (inhibitory zone diameter 22.37 mm). By the detection of stability of the crude extract to acid, alkali, heat and UV, the results demonstrated that the inhibition rate of the crude extract against Colletotrichum gloeosporioides was stable at pH 2-8 and 77.13 % of inhibition rate was still kept after treated at 140 ºC for 20 min and the crude extract had a stable activity to UV, and the inhibition rate was almost unchanged after 6 h.